Difference of interpersonal conflict management style practiced by academic administrators at Islamic higher Education Institution, Malaysia - Salleh, Mohamad Johdi; Safarali, Kadamov; Mohamad, Nazifah Alwani (IJECM Rochester, United Kingdom, 2015)
The study aims to analyze the differences of interpersonal conflict management styles practiced by the academic administrators at Islamic higher education institution. The study involved 152 academic administrators of International Islamic University Malaysia from seven kulliyyah or faculties. They comprised of Professors, Associate Professors and Assistant Professors. The study used instrument Rahim Organizational Conflict Inventory-II (2001, 2008) to measure five interpersonal conflict management styles consisting 28 items and the data were analyzed using the SPSS program version 17. The result of the study reveals that academic administrators had varying levels of practice of each style. In integrating style the mean score was 4.22 which fall into a very highly practiced style by the academic administrators. This is followed by compromising style with mean 3.85, obliging style mean 3.38, and, avoiding style mean 3.32. The study provide key results and interpretations of the research questions which were analyzed with descriptive, independent sample T-test and one way ANOVA tests in terms of gender, age, job position, work experience and academic status. The research findings are essential to the development of interpersonal conflict management competencies in achieving the National Key Result Area (NKRA), Vision 2020, and, the Malaysian Higher Education Development Plan 2015-2025.